2021
DOI: 10.1123/jsr.2020-0059
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Foam Rolling and Dynamic Stretching on Athletic Performance: A Critically Appraised Topic

Abstract: Clinical Scenario: Dynamic stretching and foam rolling are commonly used by athletes to reduce injury and enhance recovery, thereby improving athletic performance. In contrast to dynamic stretching, little research has been conducted on the acute effects of foam rolling as part of the preexercise warm-up routine. Previously, when researchers implemented foam rolling with static stretching as a warm-up, some found that foam rolling slightly improved flexibility and performance outcomes. More recent research has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
1
13
1
Order By: Relevance
“…The meta-analysis revealed no significant changes between the combined treatment and stretching alone. This is in contrast to the review by Anderson et al (2021), who concluded that foam rolling and dynamic stretching might have a superior effect compared to dynamic stretching alone. The authors reported that two out of four studies found a greater increase in vertical jump height compared to dynamic stretching alone.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…The meta-analysis revealed no significant changes between the combined treatment and stretching alone. This is in contrast to the review by Anderson et al (2021), who concluded that foam rolling and dynamic stretching might have a superior effect compared to dynamic stretching alone. The authors reported that two out of four studies found a greater increase in vertical jump height compared to dynamic stretching alone.…”
Section: Discussioncontrasting
confidence: 95%
“…However, it is not clear if the increases in ROM have an accumulated effect when foam rolling and stretching are performed within one training session, compared to foam rolling or stretching alone. Anderson et al (2021) reported in their review only a small additional effect when comparing a combined treatment with foam rolling and dynamic stretching to dynamic stretching alone. However, the authors did not perform a meta-analysis or include the static stretching technique, or consider other muscles than the hamstrings.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the other hand, agility tends to be positively impacted by stretching. Dynamic stretching can improve an athlete's power [56].…”
Section: Discussionmentioning
confidence: 99%